Aryl Methyl Ketones: Versatile Synthons in the Synthesis of Heterocyclic Compounds - Mohammed, Shabber; West, Jason S.; Mitton-Fry, Mark J. (SynOpen, 2022)
The synthesis of aromatic heterocycles has attracted substantial attention due to the abundance of these heterocycles in drug molecules, natural products, and other compounds of biological interest. Accordingly, there is a demand for straightforward synthetic protocols toward such compounds using readily available starting materials. In the past decade, there have been substantial developments in heterocycle synthesis, especially in metal-catalyzed and iodine-assisted approaches. This graphical review focuses on notable reactions from the past decade using aryl and heteroaryl methyl ketones as starting materials, including representative reaction mechanisms.
Keywords: aromatic heterocycles; iodine; ketones; metal-free; fused bicycles; fused tricycles; fused polyheterocycles